Ovarian cancer and hormone replacement therapy in the Million Women Study. - Beral, V; Bull, D; Green, J; Reeves, G (2007)
BACKGROUND: Ovarian cancer is the fourth most common cancer in women in the UK, with about 6700 developing the malignancy and 4600 dying from it every year. However, there is limited information about the risk of ovarian cancer associated with the use of hormone replacement therapy (HRT). METHODS: 948,576 postmenopausal women from the UK Million Women Study who did not have previous cancer or bilateral oophorectomy were followed-up for an average of 5.3 years for incident ovarian cancer and 6.9 years for death. Information on HRT use was obtained at recruitment and updated where possible. Relative risks for ovarian cancer were calculated, stratified by age and hysterectomy status, and adjusted by area of residence, socioeconomic group, time since menopause, parity, body-mass index, alcohol consumption, and use of oral contraceptives. FINDINGS: When they last reported HRT use, 287,143 women (30%) were current users and 186 751 (20%) were past users. During follow-up, 2273 incident ovarian cancers and 1591 deaths from the malignancy were recorded. Current users were significantly more likely to develop and die from ovarian cancer than never users (relative risk 1.20 [95% CI 1.09-1.32; p=0.0002] for incident disease and 1.23 [1.09-1.38; p=0.0006] for death). For current users of HRT, incidence of ovarian cancer increased with increasing duration of use, but did not differ significantly by type of preparation used, its constituents, or mode of administration. Risks associated with HRT varied significantly according to tumour histology (p<0.0001), and in women with epithelial tumours the relative risk for current versus never use of HRT was greater for serous than for mucinous, endometroid, or clear cell tumours (1.53 [1.31-1.79], 0.72 [0.52-1.00], 1.05 [0.77-1.43], or 0.77 [0.48-1.23], respectively). Past users of HRT were not at an increased risk of ovarian cancer (0.98 [0.88-1.11] and 0.97 [0.84-1.11], respectively, for incident and fatal disease). Over 5 years, the standardised incidence rates for ovarian cancer in current and never users of HRT were 2.6 (2.4-2.9) and 2.2 (2.1-2.3) per 1000, respectively-ie, one extra ovarian cancer in roughly 2500 users; death rates were 1.6 (1.4-1.8) and 1.3 (1.2-1.4) per 1000, respectively-ie, one extra ovarian cancer death in roughly 3300 users. INTERPRETATION: Women who use HRT are at an increased risk of both incident and fatal ovarian cancer. Since 1991, use of HRT has resulted in some 1300 additional ovarian cancers and 1000 additional deaths from the malignancy in the UK.